The Effect of Ewom, Digital Marketing, Customer Satisfaction on Customer Loyalty (Shopee Customer Survey in Pangkalan Brandan) - Bulan, Tengku Putri Lindung; Chandra, Riny (Universitas Muhammadiyah Pontianak, 2021)
Pangkalan Brandan is an area in Kabupaten Langkat that has an expenditure gap among the poor, but in the aspect of using e-commerce, it has increased. If it is related to the variables in this study, the use of technology is not cheap. The purpose of this study was to determine the effect of electronic word of mouth, digital marketing and customer satisfaction on Shopee customer loyalty at Pangkalan Brandan. The sample in this study amounted to 96 respondents. The data analysis method used is multiple linear regression analysis and proving the hypothesis is done by t test and F test. The partial test results show that electronic word of mouth has a significant effect on customer loyalty, digital marketing has a significant effect on customer loyalty and customer satisfaction has a significant effect on Shopee customer loyalty in Pangkalan Brandan. Simultaneous test results show that electronic word of mouth, digital marketing and customer satisfaction simultaneously have a significant effect on Shopee customer loyalty in Pangkalan Brandan.